Levels of Vitamin A and high and low level of roughage in the finishing ration of beef steers previously wintered on silage and limited grain - Richardson, D.; Smith, E.F.; Harbers, L.H.; Lebdosoekojo, R.S. (Kansas Agricultural Experiment Station, 2011)
Sixty Hereford steer calves averaging 440 pounds each from Warner’s Ranch in Rice County were wintered on sorghum silage, 1pound soybean oil meal and sorghum grain. Thirty received 4 pounds grain per head daily and 30 received 8 pounds.
Keywords: Beef; Vitamin A; Roughage; Silage